Carbon allocation to growth and storage in two evergreen species of contrasting successional status. Issue 5 (10th May 2017) - Piper, Frida I.; Sepúlveda, Paulina; Bustos‐Salazar, Angela; Zúñiga‐Feest, Alejandra
Abstract : PREMISE OF THE STUDY: A prevailing hypothesis in forest succession is that shade‐tolerant species grow more slowly than shade‐intolerant species, across light conditions, because they prioritize carbon (C) allocation to storage. We examined this hypothesis in a confamilial pair of species, including one of the fastest‐growing tree species in the world ( Eucalyptus globulus ) and a shade‐tolerant, slow‐growing species ( Luma apiculata ). METHODS: Seedlings were subjected to one out of four combinations of light (high vs. low) and initial defoliation (90% defoliated vs. nondefoliated) for four months. Growth, C storage concentration in different organs, leaf shedding, and lateral shoot formation were measured at the end of the experiment. KEY RESULTS: Eucalyptus globulus grew faster than L. apiculata in high light, but not in low light. Both species had lower C storage concentration in low than in high light, but similar C storage concentrations in each light condition. Defoliation had no effect on C storage, except in the case of the old leaves of both species, which showed lower C storage levels in response to defoliation. Across treatments, leaf shedding was 96% higher in E. globulus than in L. apiculata while, in contrast, lateral shoot formation was 87% higher in L. apiculata . CONCLUSIONS: In low light, E. globulus prioritized C storage instead of growth, whereas L. apiculata prioritized growth and lateral branching. Our results suggest that shade tolerance depends on efficient light capture rather than C conservation traits.